A contribuição de um dicionário histórico: o dicionário histórico do Português do Brasil - Murakawa, Clotilde de Almeida Azevedo [UNESP] (My University, 2011)
This article presents the theoretical and methodological road used to construct the Historical Dictionary of Brazilian Portuguese in the XVI, XVII and XVIII centuries (sponsored by CNPq). Starting with some examples and models of historical and diachronic dictionaries we set the model that structures the Dictionary; it has the purpose of assembling in a single book the Portuguese language lexicon responsible for the construction of the Portuguese language in Brazil. Our reference basis is a data bank with many sorts of sources existing along the three centuries of the Brazilian colonial history. This data bank provides the nomenclature of the historical dictionary and allows the construction of the lexicographical definition through its lexical context that is followed by consecrated examples. This article also presents the contributions of the dictionary to future studies of the Brazilian Portuguese.
Keywords: Historical dictionary; Lexicography; Corpus linguistics; Definition; lexicographical paper; Portuguese language history; Brazilian colonial history